Microwave-assisted synthesis of an RGO/CdS/TiO2 step-scheme with exposed TiO2 {001} facets and enhanced visible photocatalytic activity. Issue 71 (9th December 2020) - Ma, Zilun; Shi, Liyan; Qu, Wenwen; Hu, Qiong; Chen, Ruifang; Wang, Yijun; Chen, Zhen
Abstract : The photocatalytic enhancement of RGO/CdS/TiO2 is due to the high-energy {001} surface of TiO2 and CdS forming a stepped heterojunction, which is dispersed on the surface of reduced graphene oxide. Abstract : Semiconductor-based heterojunction photocatalysts with a special active crystal surface act as an essential part in environmental remediation and renewable energy technologies. In this study, an RGO/CdS/TiO2 step-scheme with high energy {001} TiO2 facets was successfully fabricated via a microwave-assisted solvothermal method. The photocatalytic performance of as-prepared samples was assessed by degrading methylene blue under visible light irradiation. We found that the photocatalytic activity of the RGO/CdS/TiO2 step-scheme heterojunction was related to the proportion of TiO2 . A ternary sample with a TiO2 content of 10 wt% exhibited superior photocatalytic performance, and approximately 99.7% of methylene blue was degraded during 50 min of visible illumination which was much higher than the percentages found for TiO2, CdS, RGO/TiO2, and RGO/CdS. The greatly improved photocatalytic performance is due to the exposure of the reactive {001} surface of TiO2 and the formation of a CdS/TiO2 heterojunction step-scheme, which effectively inhibits the recombination of charge carriers at the heterogeneous interfaces. Moreover, the incorporation of graphene further enhances the visible light harvesting and serves as an electron transport channel for rapidly separating photogenerated carriers. Based on the PL, XPS, photoelectrochemical properties and the free radical capturing experiment results, a possible photodegradation mechanism was proposed.